Task Force on Telecommunications Infrastructure in the Arctic (TFTIA), meeting 02, final participant list - Arctic Council Secretariat (Arctic Council Secretariat, 2016)
The Arctic Council’s Task Force on Telecommunications Infrastructure in the Arctic (TFTIA) was established by the second Iqaluit Declaration (2015). It held its second meeting in Tromsø, Norway in February of 2016.